2022
DOI: 10.1007/s00604-022-05570-5
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive FRET-based aptasensor for interleukin-6 as a biomarker for COVID-19 progression using nitrogen-doped carbon quantum dots and gold nanoparticles

Abstract: A label-free and specific FRET-based interleukin-6 (IL-6) aptasensor was developed using a DNA aptamer modified with nitrogen-doped carbon quantum dots (NCDs) and gold nanoparticles (AuNPs) as a donor-quencher pair. The assayed target was capable of disrupting the donor–acceptor assemblies yielding a concentration-related fluorescence recovery of NCDs ( λ em = 445 nm and λ ex = 350 nm). By designing two different probes, the interaction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 49 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…7 c). Mohamad Mahani et al [ 143 ] reported the FRET-based aptasensor for interleukin-6 as a biomarker for COVID-19 progression using nitrogen-doped carbon quantum dots and gold nanoparticles. Alhadrami et al [ 144 ] reported a colorimetric biosensor of using a cotton swab as a substrate to collect the detected S through the lactoferrin general capture agent, it could specifically bind an orange nanopolymer-modified Ab to produce an optical signature visible to the naked eye, which is available in 5 min and suitable for field detection.…”
Section: Rapid Detection Methodsmentioning
confidence: 99%
“…7 c). Mohamad Mahani et al [ 143 ] reported the FRET-based aptasensor for interleukin-6 as a biomarker for COVID-19 progression using nitrogen-doped carbon quantum dots and gold nanoparticles. Alhadrami et al [ 144 ] reported a colorimetric biosensor of using a cotton swab as a substrate to collect the detected S through the lactoferrin general capture agent, it could specifically bind an orange nanopolymer-modified Ab to produce an optical signature visible to the naked eye, which is available in 5 min and suitable for field detection.…”
Section: Rapid Detection Methodsmentioning
confidence: 99%
“…The fluorophore is spatially separated from the quencher to produce a bright fluorescence signal . By utilizing MBs, researchers have studied specific interactions between aptamers and various proteins, such as thrombin, platelet-derived growth factor (PDGF-BB), Tat protein of HIV-1, and so on. Additionally, unique optical properties make optical nanomaterials another excellent candidate to develop optical assays . By way of illustration, Ghosh’s group synthesized DNA aptamers targeting glycated albumin (GA) with a quantum dot attached at one end and gold nanoparticle quencher at the other end .…”
Section: Detection Methods Of Aptamer–protein Interactionsmentioning
confidence: 99%
“…216−218 Additionally, unique optical properties make optical nanomaterials another excellent candidate to develop optical assays. 219 By way of illustration, Ghosh's group synthesized DNA aptamers targeting glycated albumin (GA) with a quantum dot attached at one end and gold nanoparticle quencher at the other end. 220 Without the addition of GA, the aptamer folded to a hairpin loop structure and the quantum dot fluorescence was quenched by energy transfer to the gold nanoparticle.…”
Section: Optical Assaymentioning
confidence: 99%
“…Khakbaz et al reported DNA aptamer immobilized with nitrogen-doped carbon quantum dots (NCDs) based aptasensor system for selective detection of interleukin-6 (IL-6) via a fluorescence resonance energy transfer (FRET) mechanism, and in this system gold nanoparticles (AuNPs) were used as a quencher. 191 Another report also uses carbon dots and palladium−iridium nanocubes-based ratiometric fluorescent immunoassay for selective detection of cTnI with 0.31 pg/mL (LOD) sensitivity. 192 Zhang et al developed a cost-effective FRET sensing platform for the detection of B-type natriuretic peptide (BNP) using graphene oxide (GO).…”
Section: Optical Signaling Readout-based Nanobiosensorsmentioning
confidence: 99%
“…Myoglobin aptamer immobilized carbon dots were designed by Wang et al This sensing strategy has the capability of selective and sensitive detection of myoglobin in human serum, urine, and saliva with a linear range from 50 pg/mL to 100 ng/mL, and the detection limit was found to be as low as 20 pg/mL. Khakbaz et al reported DNA aptamer immobilized with nitrogen-doped carbon quantum dots (NCDs) based aptasensor system for selective detection of interleukin-6 (IL-6) via a fluorescence resonance energy transfer (FRET) mechanism, and in this system gold nanoparticles (AuNPs) were used as a quencher . Another report also uses carbon dots and palladium–iridium nanocubes-based ratiometric fluorescent immunoassay for selective detection of cTnI with 0.31 pg/mL (LOD) sensitivity .…”
Section: Optical Signaling Readout-based Nanobiosensorsmentioning
confidence: 99%